1998
DOI: 10.1093/ndt/13.11.2853
|View full text |Cite
|
Sign up to set email alerts
|

Daily home haemodialysis in the Netherlands; effects on metabolic control, heamodynamics, and quality of life

Abstract: DHHD compared to conventional thrice-weekly haemodialysis with similar weekly Kt/V results in an improved haemodynamic control and quality of life, but has lesser impact on metabolic regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
157
3
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(175 citation statements)
references
References 0 publications
11
157
3
4
Order By: Relevance
“…Similarly, the investigators from the Adequacy of Peritoneal Dialysis in Mexico study found no long-term beneficial effect in QOL by increasing peritoneal small solute clearance in their study population (23). In contrast, enthusiastic reports of improved QOL with intensive hemodialysis have been observed using before-and-after designs (24,25). In the context of the results of this study, how does one reconcile the lack of increased benefits in QOL for patients who undergo NHD compared with PD?…”
Section: Discussionmentioning
confidence: 71%
“…Similarly, the investigators from the Adequacy of Peritoneal Dialysis in Mexico study found no long-term beneficial effect in QOL by increasing peritoneal small solute clearance in their study population (23). In contrast, enthusiastic reports of improved QOL with intensive hemodialysis have been observed using before-and-after designs (24,25). In the context of the results of this study, how does one reconcile the lack of increased benefits in QOL for patients who undergo NHD compared with PD?…”
Section: Discussionmentioning
confidence: 71%
“…[46][47][48][49][50][51][52][53][54][55][56][57] The studies with strong designs included four comparative observational studies 16,42,44,45 and two systematic reviews.…”
Section: Resultsmentioning
confidence: 99%
“…4 This view has been supported primarily by small, uncontrolled studies describing very low vascular access event rates with daily and nocturnal hemodialysis. [5][6][7][8] Two nonrandomized studies suggested that, compared with conventional dialysis, daily dialysis is associated with a five-fold decrease in access complications. 9,10 However, two literature reviews suggested the opposite.…”
Section: Discussionmentioning
confidence: 99%